Plant based synthesis and characterisation of iron- and silver-doped zinc oxide nanoparticles for sonocatalytic degradation of malachite green - Chan, Yin Yin (2023)
The discharge of dye-containing wastewater such as MG from industry into environment is a hot topic among society nowadays due to the high persistent and carcinogenic effect of dye molecules. Besides, high consumption of chemical in the synthesis of nanomaterial is one of the main concerns in the research field. In this study, sonocatalysis was proposed to degrade the organic dyes using metal doped zinc oxide (ZnO) nanoparticles which were obtained via green synthesis process. Characterization of plant extract and the green synthesized ZnO samples were carried out to determine the plausible mechanism of green synthesis and their effects towards the sonocatalytic performance, respectively. The results confirmed that high phytochemical content was present in plant extract and involved in the green synthesis of ZnO nanoparticles. Metal doping successfully lowered down the band gap energy, reduced particle size as well as increased the surface area of the green synthesized ZnO nanoparticles. In this work, 5 wt% silver-doped ZnO (AgZnO) with the highest sonocatalytic activity was selected to evaluate sonocatalytic dye degradation through parameter study. By the means of response surface methodology (RSM), a central composite design (CCD) model was successfully constructed to predict the sonocatalytic degradation efficiency and the optimum degradation efficiency of MG was found to be 89.21% within 15 mins using Ag-ZnO with 0.75 g/L of catalyst loading under 500 mg/L of initial dye concentration, 40 W of ultrasonic power and 1.75 mM of oxidant concentration. The reusability test also confirmed that the green synthesized samples exhibited excellent stabilities which could retain the degradation efficiency of MG up to 76.6% even after 5 cycles of sonoctalytic reaction. The kinetic study showed that the sonocatalytic degradation of MG was fitted well into second-order kinetic model with high R2 value (0.953). Furthermore, thermodynamic study confirmed the feasibility and efficiency of sonocatalysis reaction in the degradation of MG with low value of activation energy (+ 24.43 kJ/mol) by using the green synthesized Ag-ZnO. This research marked the great breakthrough of wastewater treatment by using the green nanomaterials as a sonocatalyst.